Measurement Properties of the Dizziness Handicap Inventory—Children and Adolescents for Children and Adolescents Postconcussion. Issue 4 (October 2020) - Tiwari, Devashish; Yorke, Amy; Goldberg, Allon; Marchetti, Gregory F.; Alsalaheen, Bara
Abstract : Purpose: The purpose of this study was to examine and report the construct validity, internal consistency, and item structure of the Dizziness Handicap Inventory—Children and Adolescents (DHI-CA) in postconcussion children and adolescents. Methods: A retrospective chart review was conducted for 132 participants. Data were extracted on the DHI-CA, Sports Concussion Assessment Tool-III symptom inventory, and Vestibulo-ocular Motor Screening. The DHI-CA was examined for validity, internal consistency, and factor structure. Results: The DHI-CA had fair convergent validity ( r s = 0.30-0.40), but discriminant validity findings were inconclusive. The functional subscale demonstrated least consistent loadings and 4 items had cross-loading. Reliability analysis indicated possible item redundancy given that the overall Cronbach α was higher than the subscales. Conclusion: Despite demonstrating convergent validity, structural inconsistencies and possible item redundancy warrant further exploration and restructuring of the DHI-CA. Caution is recommended while making clinical decisions based on the DHI-CA results alone. Video Abstract: For more insights from the authors, see Supplemental Digital Content 1, available at: http://links.lww.com/PPT/A303 . Abstract : Supplemental Digital Content is Available in the Text.The specific aims of this study were to examine the construct validity, internal consistency, and t structure of items the Dizziness Handicap Inventory-Children and Adolescents in children and adolescents postconcussion.